Optimizing Human Resources Empowerment In The Era Of Covid 19: From Transactional To Transformational Leadership - Sukoco, Iwan; Evitha, Yuli; Hermanto, Bambang; Herawati, Tetty (Technium Social Sciences Journal, 2020)
There are two important things to consider in business resilience, namely market dependence (competitiveness) and industry turbulence (speed of change). In the crisis era, due to the COVID-19 pandemic, rapid changes occur in the business environment so that companies that want to survive must be able to quickly adapt. Organizational failure is usually determined by leadership or the nature of the organization itself. This research is aiming at answering the questions of how to optimize the company's human resources (HR) in the Covid 19 period and what criteria must be fulfilled so that someone is able to become a transformational leader. This study applies a case study approach from qualitative research design. In this study a semi-structured interview is used to get the perspectives of transformational leadership. The research proved that HR optimization can be implemented by improving the elements of employee engagement and employee enablement. However, to be able to improve these elements, a change in leadership style from transactional to transformational leadership must be applied. This study contributes significantly to the development of leadership knowledge, especially regarding the effectiveness of transformational leadership in advancing the company. In addition, the results of this study can be used as input for authorized organizations in the development of transformational leadership in order to optimize the company's human resources.